A study on factors affect career success among employees in Tenaga Nasional Berhad (TNB) Malacca / Fitri Nur Hidayah Sipulizan and Prisila Aren Anak Timbang - Sipulizan, Fitri Nur Hidayah; Timbang, Prisila Aren (Faculty of Business Management, 2016)
This paper presents the analysis on the factors that affect the career success among employees in TNB Malacca. The research wants to identify the relationship between job satisfactions, self-esteem and career adaptability with the career success where focused the three elements that necessarily related and act as the independent variables for this study. The three objectives are presented which is first, to identify the relationship between job satisfaction and career success among employees, second to study the effect of self-esteem and career success among the employees and the third objectives are to determine the effect on the career adaptability and career success among employees in TNB Malacca. For this purpose, 97 reliable respondents from TNB Malacca were studied. The finding showed that only two variables have significant relationship which is self-esteem and career adaptability. Thus, these two variables consider as the factors that affect the career success among employees in TNB Malacca. Meanwhile, one variable showed negative relationship is the job satisfaction which considers not the factors that affecting career success among employees. This study refers to primary data and also secondary data for supporting the sampling technique. Meanwhile, the researcher use questionnaire as the method to collect the data and information from sample respondents in accomplishing the research objectives. The result of research was analyzed using multiple statistical procedures which are reliability analysis, correlation analysis and multiple regression analysis. The results of study presented in this research agree that self-esteem and career adaptability are the most factors that affecting career success. This study can be seen as a foreword to a more detailed study to be carrying by future research on the factors of career success among employees.